Solution structure of duplex DNA containing an extrahelical abasic site analog determined by NMR spectroscopy and molecular dynamics. - Lin, Z (1998)
Translesional DNA synthesis past abasic sites proceeds with the preferential incorporation of dAMP opposite the lesion and, depending on the sequence context, one or two base deletions. High-resolution NMR spectroscopy and molecular dynamics simulations were used to determine the three-dimensional structure of a DNA heteroduplex containing a synthetic abasic site (tetrahydrofuran) residue positioned in a sequence that promotes one base deletions. Analysis of NMR spectra indicates that the stem region of the duplex adopts a right-handed helical structure and the glycosidic torsion angle is in anti orientation for all residues. NOE interactions establish Watson-Crick alignments for all canonical base pairs of the duplex. Measurement of distance interactions at the lesion site shows the abasic residue excluded from the helix. Restrained molecular dynamics simulations generated three-dimensional models in excellent agreement with the spectroscopic data. These structures show a regular duplex region and a slight bend at the lesion site. The tetrahydrofuran residue extrudes from the helix and is highly flexible. The model reported here, in conjunction with a previous study performed on abasic sites, explains the structural bias of one-base deletion mutations.